Pharmacokinetic Drug Interaction between Tofacitinib and Voriconazole in Rats - Lee, Ji-Sang (Pharmaceutics, 2021)
Fungal infections are prevalent in patients with immune diseases. Voriconazole, a triazole antifungal drug, inhibits the cytochromes CYP3A4 and CYP2C, and tofacitinib, a Janus kinase inhibitor for the treatment of rheumatoid arthritis, is metabolized by CYP3A4 and CYP2C19 in humans. Here, we investigated their interaction during simultaneous administration of both drugs to rats, either intravenously or orally. The area under the plasma concentration–time curve from time zero to time infinity (AUC) of tofacitinib was significantly greater, by 166% and 171%, respectively, and the time-averaged non-renal clearance (CL(NR)) of tofacitinib was significantly slower (59.5%) than that for tofacitinib alone. An in vitro metabolism study showed non-competitive inhibition of tofacitinib metabolism in the liver and intestine by voriconazole. The concentration/apparent inhibition constant (K(i)) ratios of voriconazole were greater than two, indicating that the inhibition of tofacitinib metabolism could be due to the inhibition of the CYP3A1/2 and CYP2C11 enzymes by voriconazole. The pharmacokinetics of voriconazole were not affected by the co-administration of tofacitinib. In conclusion, the significantly greater AUC and slower CL(NR) of tofacitinib after intravenous and oral administration of both drugs were attributable to the non-competitive inhibition of tofacitinib metabolism via CYP3A1/2 and CYP2C11 by voriconazole in rats.